Chemical analysis and nutritional assessment of fluted pumpkin (Telfairiaoccidentalis Hook F.) seed residuefed to African catfish (clariasgariepinus) at graded inclusion levels (2013)
The chemical analysis and nutritional assessment of fluted pumpkin seed residue fed to African catfish (Clariasgariepinus) at graded inclusion levels was carried out in order to evaluate its effect on the growth performance and nutrient utilization of the catfish. Five diets containing 0, 15, 30, 45 and 60% inclusion levels of fluted pumpkin seed residue (FPSR) as partial replacement for groundnut cake were prepared and fed to the fishes for eight weeks. Each treatment had three replicates with 15 fish per replicate (mean initial weight 140.87 Â± 8.77g) in 30-litre plastic tanks and fish fed at 3% of body weight twice daily. Fish on control diet showed the best growth and nutrient utilization while diets with defatted fluted pumpkin seeds cake produced weight reduction in the fish with the least reduction on diet 2 (15% inclusion) and greatest on diet 4 (45% inclusion). The specific growth rate, feed conversion ratios and protein intake of the control fish were significantly (p<0.05) higher than those on FPSR-containing diets.Histopathological reports showed some damage to the liver of fish in higher FPSR-containing rations, torn gill tissues and changes of intestinal structure. Haematological parameters like haemoglobin, erythrocyte, sedimentation rate and biochemical parameters were within the ranges for healthy fish though reduced from pre-treatment values